1986
DOI: 10.1111/j.1471-0528.1986.tb07810.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐trimester levels of alphafetoprotein in the screening of low birthweight

Abstract: Elevated maternal levels of alphafetoprotein (AFP) in midtrimester are believed by some to be a useful screening test for premature labour, low birthweight and low birthweight for gestation. In a prospective study on 887 randomly selected pregnant women we found that although there was an association between low birthweight and elevated AFP, the test would miss five out of every six cases of low birthweight and there would be nine false-positives for every case correctly identified. The test is not therefore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…In the interpretation of MAFP levels, maternal weight had been regarded as an influential factor (9). These mentioned studies on MAFP were done in the first or second trimesters (4)(5)(6)(7)15). Here we report the levels at late pregnancies without medical of obstetrical complication.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the interpretation of MAFP levels, maternal weight had been regarded as an influential factor (9). These mentioned studies on MAFP were done in the first or second trimesters (4)(5)(6)(7)15). Here we report the levels at late pregnancies without medical of obstetrical complication.…”
Section: Discussionmentioning
confidence: 83%
“…At pregnancy, interpretation of MAFP levels is useful in screening certain obstetrical or abnormal fetal conditions. High maternal alpha-fetoprotein (MAFP) levels have association with later premature labor, fetal open neural tube defect or twin pregnancies (4)(5)(6)(7). High MAFP levels are also associated with low birth weight (6-9), although not sufficiently predictive (6).…”
mentioning
confidence: 99%
“…Although various authors have found an association between abnormal concentrations of MSAFP and an adverse perinatal outcome, this marker has a minimal clinical impact in selecting women at increased risk of adverse perinatal outcome (Chard et al, 1986;Maher et al, 1994) because most of the women who deliver a compromised infant would have had a normal MSAFP level in the second trimester. Therefore, we would miss the vast majority of cases, i.e., the detection rate (=sensitivity) is low.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of multiple‐marker screening for fetal Down's syndrome, 4% of the women with an euploid fetus were found to have maternal serum human chorionic gonadotrophin (MShCG) levels higher than 2.5 MOM 2 . Follow up studies have shown that pregnant women with such an un‐explained elevation of MSAFP or MShCG are at increased risk of an adverse pregnancy outcome, such as fetal death, pregnancy induced hypertension, preterm delivery or the delivery of a small for gestational age (SGA) infant 3–7 . The cause of the unexplained abnormal analyte levels remains unclear, although it has been suggested that the concentrations of MSAFP and MShCG are a reflection of placental histology and placental function 8–10 .…”
Section: Introductionmentioning
confidence: 99%